Possible ways in research in portuguese language & its literatures - Elgebaly, Maged Talaat Mohamed Ahmed (Via Atlântica, 2020)
In this article, we revise possible paths in Luso-Brazilian language and its literatures research between the decade of 1970 until the year of 2020. We start from section of the meanings of linguistic, literary, translational, touristic and educational experiences of human language: signifying, communicating and interacting. The complexity of these experiences in Portuguese Language takes on meaning through interdisciplinary and interculturality, providing a dialogue between various cultural groups that meet through that language, or in studies and researches in this field or in a language learning.